HUBUNGAN GANGGUAN FUNGSI MOTOR DENGAN HIPERTENSI IL6 TNF NITRAT OKSIDA DAN GLUTAMAT - Darwin Amir* (Neurona Majalah Kedokteran Neuro Sains, 2012)
INTRODUCTION THE BRAIN IS ONE OF THE MAIN TARGETS OF HYPERTENSION ESPECIALLY THE MOTOR FUNCTION HOWEVER LITTLE IS KNOWN ABOUT THE ASSOCIATION HYPERTENSION TO MOTOR DYSFUNCTION ALSO THE ASSOCIATION OF INTERLEUKIN6 IL6 TNF NITRIC OXIDE AND GLUTAMATE SERUM LEVEL TO MOTOR DYSFUNCTION IS STILL CONTROVERSION